The Feminist Theology's View of Christian Doctrine - Khasib Amrullah; Devi Maria Ulfa (Universitas Darussalam Gontor, 2018)
Feminist Theology is a movement considered have altered several doctrines of ‎Christianity, by cause of their persistence calling for equality with men. Initially, the ‎movement of Feminist Theology merely demanded favors they should had it. ‎However, Feminist Theologian gone so far from the position they should be before ‎breaking decrees of Christianity. They tend to understand God through a women-‎biased point of view, since concept of God are commonly comprehended from ‎patriarchal perspective. Indeed, a true theology is what comes based on Holy ‎Scripture. Such a principle, however, is not applied by Feminist Theology, since ‎their theological view are established on Christian women experience all this time. ‎According to Feminist Theology, doctrine of Christianity suggested to prioritize ‎men rather than women and accordingly, Feminist Theology desire to reconstruct ‎it to be more slightly feminine-nuanced. Margaret D. Kamitsuka, one of Feminist ‎Theologians believes in that Feminist Theology born in a struggle and continuously ‎humiliated, before bringing about the new spiritual image and resistance discourse ‎concerning in an empowerment of women. To conclude, this paper will try to ‎reveal briefly the development and Feminist Theological view about doctrine of ‎Christianity.‎